Application of Solid Dispersion Technique in the Formulation of Gemfibrozil 600 mg Film-coated Tablets - Tuyen, Nguyen Huynh; Duyen, Huynh Thi My; Thu, Nguyen Thi Anh; Trinh, Nguyen Tran Kieu; Phi, Nguyen Cong; Yen, Tran Phi Hoang; Quan, Le Minh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2DO - 10.25073/2588-1132/vnumps.4726, 2025)
Gemfibrozil is a substance used in the treatment of hyperlipidemia. Unfortunately, it has poor solubility and high adhesiveness when tablet compressing. The study was conducted to prepare gemfibrozil 600 mg film-coated tablets that meet the dissolution specification according to USP 47. The research drug was also in vitro equivalent to the reference drug Lopid ® 600 mg and reduced punch sticking. Some methods to increase the solubility of gemfibrozil (particle size reduction, such as milling, co-milling with surfactant, and preparing solid dispersions) were investigated. The melting method of preparing solid dispersion resulted in the best efficiency using poloxamer 407 as a polymer carrier. The tablets contained excipients as 6.7% poloxamer 407, 14.6% MCC 120, 4% croscarmellose sodium, 6% crospovidone, 1% stearyl fumarate, and 1% magnesium aluminum silicate, which had been proven to have dissolution profiles equivalent to Lopid ® . On the other hand, the sticking problem was improved by using sodium stearyl fumarate as the lubricating excipient and using magnesium aluminum silicate as the absorbing excipient. The study suggested potential solutions that can be applied in preparing tablets containing active ingredients with poor solubility and causing the risk of punch sticking, such as gemfibrozil.